Regulasi dan Realitas: Tantangan Hukum dalam Mencegah Praktik Bisnis yang Tidak Adil - Muhammmad Naufal Hanif; Romi Faslah (GLOBAL SCIENTS PUBLISHER, 2025)
This article examines the regulatory challenges in addressing unfair business practices in Indonesia. The research aims to identify legal gaps, analyze their impact on market fairness, and propose policy alternatives. A qualitative descriptive method was used with literature and case study approaches. The findings indicate that while regulatory frameworks exist, enforcement mechanisms remain weak, leading to widespread violations. Recommendations include strengthening institutional capacity and revising outdated regulations.